2018
DOI: 10.3390/s18092980
|View full text |Cite
|
Sign up to set email alerts
|

Development of CdSe–ZnO Flower-Rod Core-Shell Structure Based Photoelectrochemical Biosensor for Detection of Norovirous RNA

Abstract: In this work, the CdSe–ZnO flower-rod core-shell structure (CSZFRs) was prepared by ion-exchange method. The surface of CSZFRs was modified by 3-mercaptopropionic acid (MPA), and then the DNA probe was immobilized on the surface via chemical bond between -NH2 of DNA probe and -COOH of MPA. Finally, the target norovirous (NV) RNA was combined with the probe according to the principle of complementary base pairing, resulting in a decrease of the photocurrent. The results show that the absorbance spectrum of visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The figures were reprinted with permission from refs. [ 148 , 149 ], Copyright 2018, Multidisciplinary Digital Publishing Institute (MDPI) and copyright 2017, Elsevier, respectively.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The figures were reprinted with permission from refs. [ 148 , 149 ], Copyright 2018, Multidisciplinary Digital Publishing Institute (MDPI) and copyright 2017, Elsevier, respectively.…”
Section: Figurementioning
confidence: 99%
“…The ion-exchange method was used for CSZFR preparation and the assay benefits from advantages such as speed, simplicity, and convenience. The limit of detection of the assay was reported to be 0.50 nM, with a good linear relationship between the photocurrent and the NoV RNA density in the range of 0-5.10 nM [148]. In addition, of the electrochemical systems, the SPR biosensing method is the most common type of optical sensor for the detection of noroviruses.…”
Section: Norovirusmentioning
confidence: 99%
“…The diffraction peaks related to the ZnO QDs were not observed in the XRD profile of ZT. Several reasons can account for the absence of the peaks: (1) The concentration of the ZnO QDs is low, where Han et al [23] reported a similar observation upon incorporation of CdSe QDs into the framework of ZnO flowers. (2) The effect may relate to the level of the homogeneity of the mixing of Ti and Zn components in ZT [24].…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…In these equations, , , and are the permittivity values of core, shell (of nanoparticle) and the surrounding medium, respectively. As stated before, the choice of = 3 reduces Equations ( 4)- (6) to the corresponding ordinary 3D space [40] forms.…”
Section: Model and Theorymentioning
confidence: 99%
“…More importantly, these find exciting applications in the biomedical area of research as the study includes targeted drug delivery, biosensing, bioimaging, targeted gene delivery, DNA interactions, pH nano-sensor for single cell, etc. [2][3][4][5][6][7]. In this stream, possible control over the plasmonic parameters led to the interest of the research and development community to explore varieties of electromagnetic features [8,9] of core-shell nanoparticles in different ambiance.…”
Section: Introductionmentioning
confidence: 99%